Overview of Outpatient Patient Registration Flow at Kalideres District Health Center in 2022 - Trideswira; Fannya, Puteri (International Archives of Medical Sciences and Public Health, 2023)
Community Health Centers are one of the spearheads in terms of health services that can help achieve optimal health status. This paper reviews the implementation of health services at the Kalideres District Health Center, especially related to the flow of outpatient registration where the information system should be carried out as well as possible in accordance with its main tasks and functions. The research method used qualitative and the informants in this research were 4 Medical Records Officers and 2 patients. Standard Operational Procedures The patient reception flow at the Kalideres sub-district health center has been carried out according to applicable standards, but it appears that the steps have not been detailed and there has been no evaluation. The understanding value of the importance of registration among officers at the Kalideres District Health Center is still relatively low.